1998
DOI: 10.1029/98ja02244
|View full text |Cite
|
Sign up to set email alerts
|

On the cause of a magnetospheric flux transfer event

Abstract: Abstract. We present a detailed investigation of a magnetospheric flux transfer event (FFE) seen by the Active Magnetospheric Tracer Explorer (AMPTE) UKS and IRM satellites around 1046 UT on October 28, 1984. This event has been discussed many times previously in the literature and has been cited as support for a variety of theories of FTE formation. We make use of a model developed to reproduce ion precipitations seen in the cusp ionosphere. The analysis confirms that the FTE is well explained as a brief excu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 126 publications
11
63
0
Order By: Relevance
“…As discussed in section 1, the motion and occurrence of these events have been well explained in terms of pulsed magnetopause reconnection. The repeat periods found here are also consistent with those of FTEs at the magnetopause (Lockwood and Wild, 1993) and deduced from cusp ion steps , events which are also well explained in terms of the e ects of reconnection pulses (see reviews by Hapgood, 1998 andrespectively). The ESR data presented here give us our ®rst opportunity to study the ®eld-parallel pro®les of plasma parameters in and around these events and, in particular, to compare with the predictions made for the ESR by Davis and Lockwood (1996 ± hereafter referred to as D&L) for periods when the magnetopause reconnection rate is pulsed.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…As discussed in section 1, the motion and occurrence of these events have been well explained in terms of pulsed magnetopause reconnection. The repeat periods found here are also consistent with those of FTEs at the magnetopause (Lockwood and Wild, 1993) and deduced from cusp ion steps , events which are also well explained in terms of the e ects of reconnection pulses (see reviews by Hapgood, 1998 andrespectively). The ESR data presented here give us our ®rst opportunity to study the ®eld-parallel pro®les of plasma parameters in and around these events and, in particular, to compare with the predictions made for the ESR by Davis and Lockwood (1996 ± hereafter referred to as D&L) for periods when the magnetopause reconnection rate is pulsed.…”
Section: Discussionsupporting
confidence: 74%
“…This result is consistent with analysis of the magnetopause signatures of pulsed reconnection, provided one uses the 2-dimensional reconnection pulse model of these``¯ux transfer events'' (Lockwood et al, 1995b). Detailed analysis of FTE signatures also strongly supports this two-dimensional model (Lockwood and Hapgood, 1998). Lockwood and Davis (1996) also show that longitudinal passes through cusp ion steps (see below) reveal that events cover considerable ranges of MLT.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…They suggested that the newly opened¯ux is of the form of ā ux rope of 1 R E in diameter. Lockwood and Hapgood (1998) later demonstrated that the``2D reconnection'' models of Saunders (1983) and Southwood et al (1988), in which reconnection could occur along a length of the magnetopause possibly several R E long, were in better accordance with observation. In the present study, we have found that the PIF maps out to an area in the dipole ecliptic plane of approximately 0.5 R E radially by 4 R E in azimuth.…”
Section: Comparison To Previous Worksupporting
confidence: 52%
“…Theoretical considerations of FTEs have resulted in suggestions for the possible cause of episodic bursts of reconnection at the magnetopause and in a description of their behaviour, both at the reconnection site and at their ionospheric footprint (Cowley, 1984;Siscoe and Huang, 1985;Cowley et al, 1991Lockwood, 1993;Lockwood et al, 1995;Lockwood and Hapgood, 1998). Hypotheses regarding the triggering mechanism, which predict separation times for FTEs from several to a few tens of minutes, include IMF B z¯u ctuations (Lockwood et al, 1989), spontaneous FTEs (Lockwood and Wild, 1993), and intrinsic magnetospheric system control (Kuo et al, 1995).…”
Section: Introductionmentioning
confidence: 99%